2017
DOI: 10.1186/s13049-017-0392-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel scoring system for predicting the neurologic prognosis prior to the initiation of induced hypothermia in cases of post-cardiac arrest syndrome: the CAST score

Abstract: BackgroundThe aim of this study was to develop a scoring system for identifying the post-cardiac arrest syndrome (PCAS) patients with a good potential for recovery prior to the initiation of induced therapeutic hypothermia.MethodsA multi-center, retrospective, observational study was performed. Data of a total of 151 consecutive adults who underwent induced hypothermia after cardiac arrest (77 learning cases from two hospitals and 74 validation cases from two other hospitals) were analyzed.ResultsIn the learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…The characteristics of the 94 included studies (30,200 patients) are listed in Table 2. TTM was used in 100% of patients in 68/94 (72%) studies, while 22 studies reported a percentage of TTM treatment ranging from 17.5% and 94%.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 94 included studies (30,200 patients) are listed in Table 2. TTM was used in 100% of patients in 68/94 (72%) studies, while 22 studies reported a percentage of TTM treatment ranging from 17.5% and 94%.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Target temperature varied across studies (ESM Table E3). Fifteen studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] were included for clinical examination, 12 for biomarkers [37][38][39][40][41][42][43][44][45][46][47][48], 26 for electrophysiology , and 15 for imaging [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], while 26 studies were included for more than one prognostic modality.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In section 5.2, we analyze three real datasets, PCAS dataset [11], diabetes dataset [22] and Wisconsin breast cancer dataset. The latter two datasets are published at the UCI machine learning repository.…”
Section: Resultsmentioning
confidence: 99%
“…Here we employ the logistic regression to learn a classification model. In this study, we analyzed four medical datasets: post-cardiac arrest syndrome (pcas) [11], chronic kidney disease (ckd), cervical cancer (ccancer) and cortex nuclear (cnuclear) [5]. The characteristics of each dataset are summarized in Table 2.…”
Section: Real Application : Covariate-shift Adaptation For Binary Clamentioning
confidence: 99%
“…A definitive estimation of the prognosis of PCAS patients undergoing targeted temperature management (TTM) should be performed 72 h after the return to normal body temperature according to the guideline [ 3 ]. But a few previous studies have reported the usefulness of early estimation of the prognosis in PCAS patients at the time of the arrival at the emergency department (ED) [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%